The effectiveness of the halal communication on muslim consumers' buying behaviour / Nor Hidayatun Abdul Razak ...[et al.] - Abdul Razak, Nor Hidayatun; Abd Wahab, Rahimah; Abd Jabar, Faizan; Harun, Norlaili; Samsudin, Mawarti Asyik; Abd Majid, Azeman (2013)
The effectiveness of any communication can be measured by the response given by the recipients of that communication which can either be positive or negative, This article will discuss on the effectiveness of the communication related to halal products in the mass media specifically on whether there was any resulting changes to the behaviour of the consumers with regards to the purchasing and using of halal products. Based on previous researches, it is safe to say that the degree of change in attitude in purchasing halal products is still unsatisfactory even though the level of awareness is high. Thus, this paper attempts to unravel the contributing factors to this and it is hoped that the discussion can trigger some ideas that the relevant authorities can use to increase the effectiveness of the halal communication. A positive change in attitude and behaviour among consumers can help the players in the halal industry especially small-scale producers in producing more halal products for the local market.